Latecomer state formation : political geography and capacity failure in Latin America - Mazzuca, Sebastián (Iowa Whitman series., 2021)
"A major contribution to the field of comparative state formation and the scholarship on long-term political development of Latin America. Latin American governments systematically fail to provide the key public goods for their societies to prosper. Sebastian Mazzuca argues this is because nineteenth-century Latin American state formation occurred in a period when commerce, rather than war, was the key driver forging countries. Latin American leaders pursued the benefits of international trade at the cost of long-term liabilities built into the countries they forged, notably patrimonial administrations and dysfunctional regional combinations."--